Study of Alkylglycerol Containing Shark Liver Oil: A Physico Chemical Support for Biological Effect? - Jean-Claude Debouzy; David Crouzier; Bertrand Lefebvre; Vincent Dabouis (AboutScience Srl, 2008)
Shark liver oil (SLO), is used in natural medicine as immunity stimulant, cardiovascular protector and anti ageing reagent. These properties were related with the high amounts of alkylglycerols (22%) obtained from Greenland shark liver. After a control of the mean SLO composition by NMR and MS, surface and membrane interactions and antioxidant properties were investigated using NMR, ESR and ST measurements and the in vitro consequences on erythrocytes and cells were studied. An estimation of the composition of this extract was performed. Moreover, SLO was found not haemolytic (A concentration inducing 50% haemolysis, HC 50 could not be reached) and superficial tension measurements revealed slight tension active properties. The 31 P and 2 H-NMR and ESR studies of phospholipid dispersions (dimyristoyl phosphatidyl cholin, DMPC) in the presence of SLO showed a significant increase in membrane fluidity at low temperature (below phase transition temperature) predominantly observed at the surface level. The anti oxidant activity was also confirmed, similar as that observed for vitamin E.